A case of severe relapsing sulphonylurea-induced hypoglycaemia. Issue 12 (2nd December 2019) - Mifsud, Simon; Schembri, Emma Louise; Fava, Stephen
Abstract : The authors report a case of a 64-year-old woman who was diagnosed with severe relapsing sulphonylurea-induced hypoglycaemia. Sulphonylureas are frequently used in patients with type 2 diabetes mellitus. They promote insulin secretion independent of the prevailing glucose level and thus are associated with an increased risk of hypoglycaemia. In patients with adequate renal function, gliclazide's effect lasts 10–24 hours and it is usually completely eliminated within 144 hours postdose. Since our patient suffered from chronic kidney disease, gliclazide's effect was prolonged and she was experiencing spontaneous hypoglycaemic episodes up to 21 days postomission of gliclazide. This case highlights two important aspects. Primarily, the prolonged effect of sulphonylureas in patients with impaired renal function, hence highlighting the need to be cautious prior to prescribing sulphonylureas in such patients. Secondly, the importance of prolonged observation of patients on sulphonylureas even after the initial hypoglycaemic event is corrected, due to the extended effects of such drugs.